Fatty Acid Profiles and Microplastic Pollution in Intertidal Biofilm at the Cowichan-Koksilah Estuary, Canada - Zeinab Zoveidadianpour; Pamela Brunswick; Oxana Blajkevitch; Taylor Filewood; Dayue Shang; Robert W. Elner; Tristan J. Douglas; Goetz Schuerholz; Leah Bendell; Juan José Alava; Mark Drever (Estuaries and Coasts, 2026)

Connecting Landscapes: A decision support system to facilitate conservation led development - Patrick Jantz; David W. Macdonald; Ivan Gonzalez; Andrew J. Hearn; Żaneta Kaszta; Erin L. Landguth; Dawn Burnham; Scott J. Goetz; Katherine A. Zeller; Andrew J. Loveridge; Samuel Cushman (Environmental Modelling & Software, 2025)

Impact of harmful algal bloom severity on bacterial communities in a full-scale biological filtration system for drinking water treatment - Youchul Jeon; Lei Li; Mudit Bhatia; Hodon Ryu; Jorge W. Santo Domingo; Jess Brown; Jake Goetz; Youngwoo Seo (Science of The Total Environment, 2024)

Using recent genetic history to inform conservation options of two Lesser Caymans iguana (Cyclura nubila caymanensis) populations - Thea F. Rogers; Ewan H. Stenhouse; Hannah Wilson; Morgan Pendaries; Michael W. Bruford; Matthias Goetz; Pablo Orozco-terWengel (Conservation Genetics, 2024)
The Sister Islands rock iguana ( Cyclura nubila caymanensis ) is critically endangered and endemic to the Caribbean islands Little Cayman and Cayman Brac. The Cayman Brac population and indeed the entire species is under threat from habitat destruction, invasive species, and anthropogenic impacts on the island. We assessed the genetic diversity, estimated effective population sizes, and tested for differentiation of populations between these two islands to inform potential future translocation should this be needed for the Cayman Brac population. Two mitochondrial DNA markers (cytochrome b and NADH subunit 4) and seven DNA microsatellite markers were used to assess the genetic diversity, genetic structure, demographic history, and effective population size of the two iguana populations. Mitochondrial DNA showed no genetic differentiation between populations; however, we found little to moderate divergence with microsatellites. We compared multiple demographic scenarios and revealed that ongoing gene flow is likely. The demographic history implied a significant genetic bottleneck around 10,000 years ago, coinciding with the sea level rise at the close of the last glacial period, and the start of the Holocene. Estimates of current effective population sizes indicate a small-scale number of breeders on each island of similar magnitude to the census mature population size (between 100 and 800 individuals). The relatively low differentiation between populations supports the possible development of active genetic management plans to manage the declining populations of the Sister Islands rock iguana.

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

Detectability of carbon with ChemCam LIBS: Distinguishing sample from Mars atmospheric carbon, and application to Gale crater - P. Beck; P.Y. Meslin; A. Fau; O. Forni; O. Gasnault; J. Lasue; A. Cousin; S. Schröder; S. Maurice; W. Rapin; R.C. Wiens; A.M. Ollila; et al. (Icarus, 2024)

The unique floor of Juling crater on Ceres - J. Hernandez; A. Nathues; H. Hiesinger; R. Sarkar; M. Hoffmann; W. Goetz; G. Thangjam (Planetary and Space Science, 2023)

Modeling mate choice in a small-scale community: Applying couple simulation in the U.S. and Conambo, Ecuador - Daniel Conroy-Beam; John Q. Patton; Cari D. Goetz; Aaron W. Lukaszewski; Brenda Bowser (Evolution and Human Behavior, 2023)

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Further evidence from common garden rearing experiments of heritable traits separating lean and siscowet lake charr ( Salvelinus namaycush ) ecotypes - Peter T. Euclide; Andrew Jasonowicz; Shawn P. Sitar; G. J. Fischer; Frederick W. Goetz (Molecular Ecology, 2022)
Genetic evidence of selection for complex and polygenically regulated phenotypes can easily become masked by neutral population genetic structure and phenotypic plasticity. Without direct evidence of genotype‐phenotype associations it can be difficult to conclude to what degree a phenotype is heritable or a product of environment. Common garden laboratory studies control for environmental stochasticity and help to determine the mechanism that regulate traits. Here we assess lipid content, growth, weight, and length variation in full and hybrid F 1 crosses of deep and shallow water sympatric lake charr ecotypes reared for nine years in a common garden experiment. Redundancy analysis (RDA) and quantitative‐trait‐loci (QTL) genomic scans are used to identify associations between genotypes at 19,714 single nucleotide polymorphisms (SNPs) aligned to the lake charr genome and individual phenotypes to determine the role that genetic inheritance plays in ecotype phenotypic diversity. Lipid content, growth, length, and weight differed significantly among lake charr crosses throughout the experiment suggesting that pedigree plays a large roll in lake charr development. Polygenic scores of 15 SNPs putatively associated with lipid content and/or condition factor indicated that ecotype distinguishing traits are polygenically regulated and additive. A QTL identified on chromosome 38 contained >200 genes, some of which were associated with lipid metabolism and growth, demonstrating the complex nature of ecotype diversity. The results of our common garden study further indicate that lake charr ecotypes observed in nature are predetermined at birth and that ecotypes differ fundamentally in lipid metabolism and growth.

The timing of anadromous bull trout migrations in estuarine and marine waters of Puget Sound, Washington - F. A. Goetz; E. Beamer; E. J. Connor; E. Jeanes; C. Kinsel; J. W. Chamberlin; C. Morello; T. P. Quinn (Environmental Biology of Fishes, 2021)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Genetic diversity and cryptic population re-establishment: management implications for the Bojer’s skink (Gongylomorphus bojerii) - Sarah J. du Plessis; Joanna Howard-McCombe; Zoe E. Melvin; Eleanor C. Sheppard; Isa-Rita M. Russo; Rouben Mootoocurpen; Matt Goetz; Richard P. Young; Nik C. Cole; Michael W. Bruford (Conservation Genetics, 2019)

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

What goes up must come down: Diel vertical migration in the deep‐water sablefish ( Anoplopoma fimbria ) revealed by pop‐up satellite archival tags - Frederick W. Goetz; Andrew J. Jasonowicz; Steven B. Roberts (Fisheries Oceanography, 2018)
The sablefish ( Anoplopoma fimbria ) is a long‐lived species with wide distribution throughout the North Pacific Ocean. While adult sablefish are considered a deep‐water fish, diet analyses suggest that they undergo vertical migrations that could be related to prey movement and feeding. Pop‐up satellite archival tags (PSATs) were used to observe the fine‐scale depth selection behavior of adult sablefish tagged off the Washington coast during the summer from June to August. Tags were physically retrieved after they surfaced using direction‐finding equipment so that complete datasets over the entire deployment were obtained from 14 tags. PSATs that recorded depth and temperature every 4 min during the deployment confirm that sablefish inhabit depths of 750 m or greater. However, a majority of the tagged fish underwent extensive vertical migrations that averaged 254.4 m overall and occurred at a 24 hr periodicity. Variations were observed among individuals in the amount of the deployment during which vertical migrations occurred, ranging from 12.37% to 63.48% of the time. During the vertical migration, fish ascended towards the surface at night and descended prior to daylight (i.e., diel vertical migration). Sablefish generally inhabited temperatures of 5°C but during the vertical migrations were found at temperatures from 6 to 10°C. Sablefish are opportunistic feeders with a large proportion of their diet being fish, euphausiids and cephalopods. Because these prey items also exhibit diel vertical migrations, it is possible that the vertical migratory behavior displayed by the sablefish was in response to the movements or the location of their prey.

Ecosystem responses to climate change at a Low Arctic and a High Arctic long-term research site - John E. Hobbie; Gaius R. Shaver; Edward B. Rastetter; Jessica E. Cherry; Scott J. Goetz; Kevin C. Guay; William A. Gould; George W. Kling (Ambio, 2017)

Dimethylsulfoniopropionate (DMSP) Increases Survival of Larval Sablefish, Anoplopoma fimbria - Jonathan S. F. Lee; Rachel S. Poretsky; Matthew A. Cook; Jose J. Reyes-Tomassini; Barry A. Berejikian; Frederick W. Goetz (Journal of Chemical Ecology, 2016)

Projected Tree Species Redistribution Under Climate Change: Implications for Ecosystem Vulnerability Across Protected Areas in the Eastern United States - Scott G. Zolkos; Patrick Jantz; Tina Cormier; Louis R. Iverson; Daniel W. McKenney; Scott J. Goetz (Ecosystems, 2015)

Comparative susceptibility among three stocks of yellow perch, P erca flavescens ( M itchill), to viral haemorrhagic septicaemia virus strain IV b from the G reat L akes - W Olson; E Emmenegger; J Glenn; J Winton; F Goetz (Journal of Fish Diseases, 2013)
The G reat L akes strain of viral haemorrhagic septicaemia virus IV b ( VHSV ‐ IV b) is capable of infecting a wide number of naive species and has been associated with large fish kills in the Midwestern U nited S tates since its discovery in 2005. The yellow perch, P erca flavescens ( M itchill), a freshwater species commonly found throughout inland waters of the United States and prized for its high value in sport and commercial fisheries, is a species documented in several fish kills affiliated with VHS . In the present study, differences in survival after infection with VHSV IV b were observed among juvenile fish from three yellow perch broodstocks that were originally derived from distinct wild populations, suggesting innate differences in susceptibility due to genetic variance. While all three stocks were susceptible upon waterborne exposure to VHS virus infection, fish derived from the M idwest (Lake Winnebago, WI ) showed significantly lower cumulative % survival compared with two perch stocks derived from the East Coast ( P erquimans River, NC and C hoptank River, MD ) of the U nited S tates. However, despite differences in apparent susceptibility, clinical signs did not vary between stocks and included moderate‐to‐severe haemorrhages at the pelvic and pectoral fin bases and exophthalmia. After the 28‐day challenge was complete, VHS virus was analysed in subsets of whole fish that had either survived or succumbed to the infection using both plaque assay and quantitative PCR methodologies. A direct correlation was identified between the two methods, suggesting the potential for both methods to be used to detect virus in a research setting.

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Immunocytochemical and biochemical detection of EMMPRIN in the rat tooth germ: differentiation-dependent co-expression with MMPs and co-localization with caveolin-1 in membrane rafts of dental epithelial cells - W. Schwab; H. Harada; W. Goetz; M. Nowicki; M. Witt; M. Kasper; K. Barth (Histochemistry and Cell Biology, 2007)

Characterization of a highly inducible novel CC chemokine from differentiated rainbow trout (Oncorhynchus mykiss) macrophages - S. MacKenzie; C. Liarte; D. Iliev; J. V. Planas; L. Tort; F. W. Goetz (Immunogenetics, 2004)

Molecular analysis of two cytochrome P450 monooxygenase genes required for paxilline biosynthesis in Penicillium paxilli, and effects of paxilline intermediates on mammalian maxi-K ion channels - L. K. McMillan; R. L. Carr; C. A. Young; J. W. Astin; R. G. T. Lowe; E. J. Parker; G. B. Jameson; S. C. Finch; C. O. Miles; O. B. McManus; W. A. Schmalhofer; M. L. Garcia; et al. (Molecular Genetics and Genomics, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Molecular characterization and sequencing of antifreeze proteins from larvae of the beetle Dendroides canadensis - J. G. Duman; N. Li; D. Verleye; F. W. Goetz; D. W. Wu; C. A. Andorfer; T. Benjamin; D. C. Parmelee (Journal of Comparative Physiology B, 1998)